Characterization of some Goat Populations in Ethiopia by means of Blood Protein Polymorphism - Simachew, Addis (2002)
Goat constitute some 22% of the ruminant livestock population in Ethiopia and are a valuable source of milk and milk products, meat, manure, skin and security and play a role in certain traditional and ceremonial functions. Goats in Ethiopia are kept in a wide range of production systems reflecting the diversity of the environment. To use these national goat resources in sustainable and rational development programs, a systematic, reliable and comprehensive breed characterization is essential. Characterization at the genetic level is the objective way to identify and quantify the available genetic diversity. The objective of this study was to assess the genetic variation among some goat populations in Ethiopia by means of blood protein polymorphisms. A total of 298 animals from four indigenous goat types (Afar, Hararghe Highland, Western Highland and Western Lowland), two exotic breeds (Toggenburg and Anglo-Nubian) and three crossbreed populations (crosses between the exotic breeds and Hararghe Highland and Somali goat types) were investigated. The red cell lysates and plasma proteins were analyzed by starch gel electrophoresis. From a total of five loci studied, two were polymorphic in, at least one population. Two alleles were detected in the loci Haemoglobin (Hb) and Transferrin (Tf). Only one allele was detected in the loci Carbonic anhydrase (CA), Albumin (Al) and Post Transferrin (PTF) in all populations of goats studied. In most cases, the observed genotypic frequencies were not significantly different from that expected under the Hardy-Weinburg equilibrium. The proportion of polymorphic loci (P) varied between 20.0% and 40.0%, mean number of alleles per locus were between 1.2 and 1.4, mean expected heterozygosities (HE) were between 0.030 and 0.177 while mean observed heterozygosities (Ho) were between 0.032 and 0.217. From the three populations of goats, higher variability was found in crossbred populations. Afar goat type was found to be more variable (H0=6.7%) among the indigenous goat types. Cluster analysis based on Nei’s (1972) standard genetic distance and the UPGMA dendrogram revealed low level of genetic distance among populations. The results indicated that a larger proportion of the genetic variation was between populations and there was high genetic similarity within populations in general but more so in indigenous goat types.